Duodenal gangliocytic paraganglioma showing lymph node metastasis: A rare case report - Sasai Daisuke; Hasegawa Chikako; Wakayama Megumi; Mituda Aki; Tuchiya Masaru; Yokose Tomoyuki; Okubo Yoichiro; Nemoto Tetsuo; Shibuya Kazutoshi (BMC, 2010)
Abstract We describe a case of duodenal gangliocytic paraganglioma showing lymph node metastasis. A 61-year-old Japanese man underwent pylorus preserving pancreaticoduodenectomy to remove a tumor at the papilla of Vater. The section of the tumor extending from the mucosa to submucosa of the duodenum was sharply demarcated, solid, and white-yellowish. Neither necrosis nor hemorrhage was present. Histological examination confirmed the immunohistochemical identification of three components comprising epithelioid cells, spindle-shaped cells, and ganglion-like cells. Epithelioid cells showed positive reactivity for synaptophysin, somatostatin, and CD56. In contrast, spindle-shaped cells showed positive reactivity for S-100 protein, but not for synaptophysin, somatostatin or CD56. Furthermore, we found lymph node metastasis despite lack of bcl-2 and p53 expression. In addition to the rarity of the tumor, we are describing here the present case suggests the malignant potency of the tumor despite lack of acceptable prognostic indicators for neuroendocrine tumor.